Disagreeing in context - Marques, Teresa (Frontiers in Psychology, 2015)
This paper argues for contextualism about predicates of personal taste and evaluative predicates in general, and offers a proposal of how apparently resilient disagreements are to be explained. The present proposal is complementary to others that have been made in the recent literature. Several authors, for instance (López de Sa, 2008; Sundell, 2011; Huvenes, 2012; Marques and García-Carpintero, 2014; Marques, 2014a), have recently defended semantic contextualism for those kinds of predicates from the accusation that it faces the problem of lost disagreement. These authors have proposed that a proper account of the resilient disagreement in the cases studied is to be achieved by an appeal to pragmatic processes, and to conflicting non-doxastic attitudes. It is argued here that the existing contextualist solutions are incomplete as they stand, and are subject to objections because of this. A supplementation of contextualism is offered, together with an explanation of why failed presuppositions of commonality (López de Sa), disputes over the appropriateness of a contextually salient standard (Sundell), and differences in non-doxastic attitudes (Sundell, Huvenes, Marques, and García-Carpintero) give rise to conflicts. This paper claims that conflicts of attitudes are the reason why people still have impressions of disagreement in spite of failed commonality presuppositions, that those conflicts drive metalinguistic disputes over the selection of appropriate standards, and hence conflicting non-doxastic attitudes demand an explanation that is independent of those context dependent pragmatic processes. The paper further argues that the missing explanation is 2-fold: first, disagreement prevails where the properties expressed by taste and value predicates are response-dependent properties, and, secondly, it prevails where those response-dependent properties are involved in evolved systems of coordination that respond to evolutionarily recurrent situations.